Inkondlo kaZulu - Vilakazi, Benedict Wallet; Zondi, Mpume; Khumalo, Langa (Wits University Press, 2021)
Inkondlo kaZulu (Zulu Poems), the first volume of poetry by B. W. Vilakazi, was first published in 1935. This was the first book of poems ever published in isiZulu; it also marked the launch of the newly established Bantu (later, African) Treasury Series, a collection of twenty classic works written between 1935 and 1987 in African indigenous languages. It contains superb nature poems and also reflects Vilakazi's contact with Western modernity. As both a traditional imbongi (bard) and a forward-looking poet who could fuse Western poetic forms with Zulu izibongo (praise poetry), he used his writings to express his resistance to the realities of capitalist exploitation of African labour and the appalling injustices of the migrant labour system. By committing to writing in poetic form what had traditionally been conveyed orally from one generation to the next, he preserves for future generations deep philosophical and emotional experiences of Zulu society. The republication of Inkondlo kaZulu affords the reader the opportunity to reappraise Vilakazi's intellectual significance and his renown as the 'father of Nguni literature' at a time when the need is acutely felt to unshackle ourselves from ethnic boundaries and break the invisible chains of inherited prejudice.